The influence of the arrangement scheme of vertical soil-cement elements of the soil base reinforcement on their joint work with the strip stamp (Academic journal Industrial Machine Building Civil Engineering, 2023)
The characteristics and parameters for modeling the soil base under the strip stamp with variable parameters of the vertical soil base reinforcement are given. Variants of soil-cement element placement with varying reinforcement ratio are presented. Differences in graphical results are shown on the example of longitudinal and transversal cross. Graphs of dependences of pressures on the soil base according to numerical modeling using HSM model and volumetric soil elements on the reinforcement ratio for different variants for of the arrangement scheme of SCE are shown. The effective zones of soil work of strip foundations (stamps) under the considered soil conditions for each of the options for placement of SCE have been identified
Keywords: vertical soil base reinforcement; vertical soil-cement element; reinforcement ratio; soil-cement soil base; tray experiment; finite element method; settlements; weak soil base; strip stamp; numerical simulation